Efficiency of private pension companies in turkey using data envelopment analysis (DEA) - (:unkn) unknown (Springer, 2016)
This paper tries to examine the efficiency of private pension companies in Turkey using Data Envelopment Analysis (DEA) covering the year 2008–2012. Total stockholders’ equity and operating expenses of the pension companies have been taken as input variables whereas investment income and fund administration charges were considered as output variables. The findings imply that there are technical efficiency gains in some private pension companies in Turkey. Though there is no continuous trend towards an improvement in technical efficiency, important changes over time have been witnessed. This may be due to the immaturity of the private pension industry given that it has launched operations 10 years ago. Note ought to be taken that management of the private pension scheme is a complex undertaking and in some instances, really chaotic. This is premised on the fact that some end up missing out on the true value of the scheme and that they even lose trust of the same. This paper thus explores the efficiency imbedded within private pension companies using Data Envelopment Analysis. © Springer International Publishing Switzerland 2016.
Keywords: Data envelopment analysis; Private pension companies; Technical efficiency